PELAKSANAAN PERAN PERAWAT SEBAGAI ADVOKAD DALAM PEMBERIAN INFORMED CONCENT TINDAKAN ECT PREMEDIKASI DI RSJD Dr. AMINO GONDHOUTOMO PROVINSI JAWA TENGAH - -, Kandar; Suryani, Maria; -, Tofi’ah (Universitas Muhammadiyah Semarang, 2015)
Background: ECT is a medical procedure performed on a patient with bipolar disorder and unipolar. Permenkes 290 / Menkes / PER / III / 2008, regarding 2, verse 1 describes